A conspiracy to commit genocide : anti-fertility research in apartheid's chemical and biological weapons programme - Jackson, M (Oxford University Press, 2015)
In late 2013, the Health Professions Council of South Africa found Dr Wouter Basson guilty of unprofessional conduct. The charges stemmed from Basson’s time as head of apartheid South Africa’s chemical and biological weapons programme - a programme implicated in kidnappings, poisonings and murders. Very little attention has been paid to a different aspect of the programme - anti-fertility research. This article argues that testimony from the Truth and Reconciliation Commission founds a reasonable basis to believe that scientists at the programme and their principals were engaged in a conspiracy to commit genocide - a conspiracy to surreptitiously deliver anti-fertility drugs to black South Africans with the intention of curtailing birth rates. A conspiracy of this kind gives rise to individual criminal responsibility under international criminal law and, given South Africa’s approach to the incorporation of international crimes, may be prosecuted as such in a domestic court. Regardless of whether it would be a good idea to prosecute the conspirators now, 30 years after the fact, South Africa’s research into anti-fertility drugs ought to play a far greater role in contemporary discussions of apartheid-era wrongs.